Penerapan Metode Cost Plus Pricing Dalam Keputusan Penentuan Harga Jual (Survey Lambemu Kota Bengkulu) - Andini Utari Putri; Vhika Meiriasari; Puspa Djuita (Jurnal Ilmiah Ekonomi Global Masa Kini, 2022)
This research is a descriptive qualitative research. The type and source of data in this study is qualitative data using secondary data, namely by making observations or observations and documentation in the form of records of production costs needed for calculating the cost of production and calculating the selling price for expenses in 2021. The research method used in this study This is a qualitative method by analyzing by collecting data and the results describe how Lambe Cake applies the cost plus pricing method in setting selling prices through observation and document analysis at Lambe Cake in Palembang City. The calculation of the cost of production is something that needs to be considered in determining the selling price of a product. Calculation of the right and accurate cost of production is something that needs to be done by every company, because without a precise and accurate calculation of the cost of production, the manufacturing company concerned will experience problems in determining the selling price of a product. The costs incurred in the production process will be used as the basis for determining the selling price and usually the company will add the desired profit percentage. One method of determining the selling price, in which all costs or full total costs are added to the profit percentage expected by the company is called the Cost Plus Pricing method. The cost of production in industrial companies consists of raw material costs, direct labor costs and factory overhead costs. In this research conducted at Lambe Cake, Bengkulu City. Lambemu here still uses calculations based on ordinary calculations according to the seller himself and does not take into account the costs associated with non-production. So it has a difference between ordinary calculations and calculations using the cost plus pricing method. By using cost plus pricing, determining the selling price becomes more accurate and precise.